TRANSPORT OF OIL AND OIL SECURITY (Perner's Contacts, 2016)
Despite the continuous search for alternative sources of energy for the life of the mature society, include still first place in its acquisition of the oil. In addition to its mining is an extremely important effective way for its transportation, since it is loca-ted only in a certain territory and into other countries must be transported. For this reason, each country aims on its own oil security, building emergency stocks and the management system of a safety of the state. Due to the tense economic and political situation, the efficiency of transport of crude oil and building a management system for emergency stocks of crude oil and petroleum products, becomes an important first safety system of each country.
Keywords: oil; transport; emergency stocks; the status of the oil shortage